The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1979
DOI: 10.1007/bf02010505
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of copper on bacteria related to the free ion concentration

Abstract: Cu(2+) ion determinations were carried out in complex and in inorganic salts-glycerol media, to which increasing amounts of Cu(II) had been added, with the ion-specific Cu(II)-Selectrode. Likewise, complexing capacity of bacterial suspensions was estimated by titration with CuSO4.Copper-sensitive bacteria, e.g.,Klebsiella aerogenes, were inhibited in their growth and survival in the range of 10(-8)-10(-6) M Cu(2+) ion concentrations. In copper-buffered complex media, high copper loads could be tolerated, as gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
86
0
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(93 citation statements)
references
References 7 publications
6
86
0
1
Order By: Relevance
“…In addition, Zevenhuizen et al (1979) The change in pH was monitored for the experiments at copper sulfate pentahydrate doses of 1 mg·L −1 , 1.5 mg·L −1 , and 2 mg·L −1 , and the results are shown in Figure S6 of the Supplementary Information. The pHs were found to reduce from an initial 7.4 to 6.2 at the end of the experiments for all the studied cases.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Zevenhuizen et al (1979) The change in pH was monitored for the experiments at copper sulfate pentahydrate doses of 1 mg·L −1 , 1.5 mg·L −1 , and 2 mg·L −1 , and the results are shown in Figure S6 of the Supplementary Information. The pHs were found to reduce from an initial 7.4 to 6.2 at the end of the experiments for all the studied cases.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 115 strains produced the expected amplicon whereas others (including all historical strains) and the negative control (H 2 O) did not. Phenotypic tests were carried out on low-complexing mineral salts casitone-yeast extract-glycerol-agar (CYE) plates (Zevenhuizen et al 1979) flooded with bacterial suspensions (≈5 × 10 6 cfu ml -1 ) in sterile tris buffer (pH 7.2), allowed to dry for 15 min., inoculated with a sterile …”
mentioning
confidence: 99%
“…Both in laboratory studies and in field studies, it has been shown that the toxicity of a given metal depends on species and chemical properties as well as environmental factors (e.g., adsorption to solid surfaces, complexation, or precipitation) (22,26,34,43,57). Heavy metal toxicity is also known to interfere with important microbial processes including aerobic and anaerobic degradation of organic matter (3,28,41).…”
mentioning
confidence: 99%